Predicting ipsilateral supraclavicular lymph node pathological complete response: nomogram based on the inflammatory markers - Zhou, Chen; Wu, Xian; Lin, Rongruo; Xu, Li; He, Tao; Yi, Jinzhi; Lv, Qing (Frontiers in Oncology, 2024)
BackgroundThe prediction of ISLN pCR after neoadjuvant chemotherapy (NAC) based on inflammatory markers and its prognostic value have rarely been investigated.MethodsPatients diagnosed with ISLN-involved breast cancer who received NAC in West China Hospital between September 2009 and December 2020 were enrolled in the derivation cohort for model construction and survival analysis, and patients with the same criteria between January 2021 and July 2024 were involved in validation cohort for external validation. After randomly dividing patients into training and testing groups at 7:3 ratio, a nomogram predicting ISLN pCR was constructed based on logistic regression in training group. Internal validation was performed in the testing group and external validation was performed in the independent validation cohort. The ROC curves were applied to validate the accuracy of the model. Survival analysis was performed using Kaplan−Meier plots.ResultsA total of 120 eligible patients were involved in the derivation cohort to establish the nomogram (84 patients in training group and 36 patients in testing group), and 45 patients were involved in the independent validation cohort for external validation of the nomogram. Pretreatment NLR and hormone receptor (HR) status, as well as preoperative SII, CEA, CA15-3 and anti-HER2 therapy were included in the nomogram predicting ISLN pCR. The AUC were 0.906 (95% CI 0.837-0.975, P<0.001), 0.888 (95% CI 0.751-1.000, P<0.001) and 0.828 (95% CI 0.703-0.953, P< 0.001) in training, testing groups and the validation cohort respectively. ISLN pCR was significantly associated with better prognosis (all P<0.05).ConclusionInflammatory factors combined with tumor makers, hormone receptor status and anti-HER2 therapy could predict ISLN pCR effectively, which was significantly associated with improved survival outcomes.